Feeder Load Balancing in Three Phase Distribution Systems - Mishra, Sujeet (IIT BHU VARANASI, 2019)
Distribution system brings electricity to the end consumers. Conventionally, it did not have any generating resources embedded in it. Thus, in conventional dis tribution system power flows are expected to be unidirectional. The distribution systems are commonly modelled as radials of certain length distributing power in one direction i.e. from source end to the load ends. The issues such as safety, protection and coordination, network planning and operation, power quality and design of system components are dictated by this radial architecture of the distri bution systems. Though, radial distribution architecture is simplest and cheapest, double cir cuit or loop architecture gives redundancy in the system. Modern distribution systems have embedded/active generations, and bidirectional flows. The possi bility of bidirectional flows has given rise to several challenges for the protection of distribution systems. This complexity of modern distribution systems calls for intelligent distribution management systems (DMS) having large amount of In formation and Communication Technology (ICT) components. The deployment of intelligent DMS has also given way to operation of the distribution systems in meshed configuration. A distribution system serves unbalanced three-phase, two-phase and single phase loads. A physical transmission happens over untransposed conductors. This fact along with variation in the types of loads naturally makes the distribution sys tems characteristically unbalanced. Other problems associated with distribution systems are under-voltage and over-voltage. The increase in voltage above 110% of the nominal voltage for more than 1 minute is termed as over-voltage. This phenomenon usually occurs due to improper compensation and outage of heavi iiily/lightly loaded lines. The under voltage limits are below 90% of the nominal voltage for more than 1 minute. The under-voltage phenomenon is quite common in distribution systems due to its radial configuration especially at the far ends of distribution systems. There are several research papers in the literature addressing the mitigation of under-voltage / over- voltage problems through reactive power compensation. Capacitive compensation can also be seen from the perspective of power factor correction in the system, as the present distribution systems caters mostly the lagging loads. The low power factor forces high currents in the sys tems calling for larger conductor sizes and larger equipment sizes and increase in system losses. Higher currents at low power factors also adversely affect voltage regulation. The problem of under-voltage/over-voltage and losses may also be addressed through reconfiguration of distribution network. Reconfiguration is essentially done using tie-lines provided in the system for redundancy against faults to ensure service of loads by rerouting the power to the systems loads in the event of line outages. The rerouting may result in a new configuration giving lower losses hence option of reconfiguration can also be exercised for loss minimization. Other problems associated with distribution systems are voltage sag/swell which are short-time (greater than 10 ms and less than 60 s) phenomenon. Re duction in voltage level in the range of 10 to 90 % of the nominal RMS voltage is considered as voltage sag and rise in voltage from 110 to 180 % is termed as voltage swell. Voltage swells are usually caused by system switching operations, sudden change in ground reference, single line-to- ground fault leading to voltage rise in unfaulted phases for the duration of fault. Similarly sags are caused by faults on distribution networks, faults on consumer equipment, and switching in of heavy loads. Other short-time phenomena in distribution systems are voltage interrup tion, voltage transients, voltage fluctuations and flicker, dc offset, and harmonic distortions. Increased presence of small generating resources embedded within distribution systems has made many of the assumption incorrect with regards to the radial nature of the distribution systems. Distribution networks are no longer ivpassive networks; thus basic premise that a radial feeder would become dead upon opening of breaker, cannot be taken for granted as embedded generation would still be feeding the line (we can discuss these in future work). The fact that variation in the types of loads naturally makes the distribution systems characteristically unbalanced, affects the distribution system in various ways. The working of several relays in the distribution systems are sensitive to the sequence currents in the systems and have a tendency to maloperate. Unbalance of phases in the distribution systems can manifest in the form of current unbalance and/or voltage unbalance. The voltage unbalance in the system can happen due to unbalance of parameters of components such as generators, transformers, and feeders (due to untransposed lines). The voltage unbalance also occurs due to un balanced phase currents leading due to asymmetrical voltage drops in individual phases. Thus current unbalance also leads to voltage unbalance. Current unbal ance mainly occurs due to single phase loads or two-phase loads and also occurs in balanced load condition in the presence of voltage unbalance. Thus these two phenomena are tied together. The main substation transformers are one of the costliest devices in the dis tribution system. The MVA capacity is divided equally on three phases hence, the per-phase capacity is one-third of the MVA capacity of the transformer. As the time progresses the system load grows, however usually the load growth may not be equal on three phases. When the system loads are severely unbalanced, then if any of the phases gets loaded up to its capacity, the further loading of the main transformer gets restricted even when there may be sufficient capacity available on other two phases. This may lead to load shedding on the loaded phase. Thus, in any system the load shedding limit would always be less than the total MVA capacity of the transformer. The phase unbalance in a system can create large voltage differences among the phases at a bus. The unbalanced phase voltages lead to unbalanced currents in three-phase loads at the customer site. This further restricts the transformer capacity at the customer site. Also, the unbalanced three phase load means higher negative- and zero-sequence current leading to losses for consumers which is not vdue to consumer. Also, in several cases the severe unbalance may not allow the consumer to use the machinery effectively because the voltage unbalance results in reverse magnetic fields which in turn results in rise of the temperature of ma chine winding and fall in the output torque. The unbalance in the system creates negative- and zero-sequence currents to flow in the system. The neutral conductor in the system is designed to carry small current compared to other phases assum ing that the phases are balanced. The increased unbalance may ask for increased rating of neutral conductors. The neutral has a higher resistance compared to other phases and therefore, increase in neutral current increases the neutral losses also. Distribution systems are getting equipped with Information and Communi cation Technologies (ICT). Various problems of distribution systems which were considered acceptable in conventional distribution systems have now become solv able. The problem of phase unbalance was not much severe as the amount of load served were less, also the protection philosophy was quite systems and unbalance was not seen as a major hindrance to the system operation. As the distribution systems grew in size, capacity, and in terms of information and communication infrastructure, the problem of unbalance became significant as well as solvable. This work considers the availability of communication, control and computa tional infrastructure for solving the problem of unbalance in distribution systems. The objective of the thesis can be enumerated as follows. 1. Development and testing of reliable and robust three-phase power flow algorithm for unbalanced systems. The developed power flow is envisaged to have capacity to handle large number of PV buses which would be feature of upcoming distribution systems. 2. Development of phase balancing algorithm for conventional distribution systems considering switchability of loads from one phase to the other. Further, the test of efficacy of the developed algorithm is to be carried out in terms of amount of un balance mitigation. 3. Development of phase balancing algorithm for distribution systems with large number of embedded single-phase generations. Further, the test of efficacy of the developed algorithm is to be carried out in terms of amount of unbalance mitigation. viOutline of the thesis is as follows. Chapter 1 introduces the topic of the thesis along with survey of relevant literature. In chapter 2, an improved CINR load flow method has been presented. The developed load flow uses the new equations to model the PV bus in current injection power flow formulation, which is based on real and imaginary parts of simple multiplication of voltages and currents of PV buses. The new CINR load flow technique decreases the required number of equations and also recovers the convergence property of revised current injection load flow methods same as conventional NR (CNR) method in the case of PV nodes particularly. At heavy load and large R/X ratio conditions also the convergence characteristics improved. The results have also demonstrated that the computation time of Mod-CINR is less than the fast decoupled NR (FDBX) methods in the absence of PV buses in systems. All the experiments suggest that the performance of the improved method in comparison with other techniques is better in terms of convergence, efficiency, sensitivity, and reliability. In chapter 3, the optimization techniques used in the chapter 4 and 5 have been described in the context of the problem addressed in the thesis. In the chapter 4, it has been demonstrated that re-phasing is sensitive to voltage-dependency of loads. It was found that the voltage improvement due to re-phasing increases the load demand. The increase in load demand at individual buses may be insignificant, but for a system as a whole it is significant enough to reverse the advantage of loss reduction conventionally expected due to re-phasing. It was found that the system after re-phasing may suggest more MVA margins at the main substation if appropriate load model is not considered. Two optimization algorithms, i.e., PSO and Butterfly Optimizer (BO), have been successfully applied for feeder re-phasing of radial distribution network. The PSO based method was compared with GA based method on a system reported in the literature to establish the effectiveness of the approach. To further validate the effectiveness of the proposed approach a 24-hour load pattern was taken. It was found that the system could be balanced substantially in terms of phase currents, phase voltages and losses per phase. In chapter 5, DG planning for the purpose of phase balancing has been pro posed. The planning is approached in two stages. In stage 1, the optimal DG viilocations (phase and bus) and sizes are obtained for peak load scenario. The loca tion are then considered to be fixed and the sizes obtained are taken as maximum available DG real and reactive capacity at the given buses. In the stage 2, the DGs are optimally scheduled hourly (in term of phase and size) for 24-hour loading sce nario to obtain the phase balancing. It has been established that an effective phase balancing can be achieved with help of single-phase DGs scheduled in this fashion. The reduction in losses and the improved voltage profile are added advantages. Detailed analysis to ascertain the effect of voltage dependency of loads on optimal scheduling of DGs establishes that for pragmatic optimal solutions, the voltages dependency of loads must be considered albeit in approximate sense rather than doing the same using constant power load model. In this chapter also BO and PSO have been successfully applied for single phase DG re-phasing of radial distribution network.
Keywords: Feeder Load Balancing; Phase Distribution Systems